The Death Penalty in Extraordinary Crimes: A Study on Killing Deception (Qatl al-Ghīlah) - Gunaldi Ahmad; M. Atho Mudzhar; Maskur Rosyid; Mhd Rasid Ritonga (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to analyze the death penalty against qatl al-ghīlah and its relevance to positive law in Indonesia. Regardless of the debate, the death penalty in Islamic criminal law and positive Indonesian law still recognizes it as a punishment for murder. One of the four types of murder in Islamic criminal law is murder by deception (qatl al-ghīlah). It is similar to premeditated murder but differs in the method and process. This study used the qualitative method in the form of normative juridical research. This study found that, first, qatl al-ghīlah is a type of murder that does not open room for forgiveness, so qiṣāṣ is the only punishment. Second, qatl al-ghīlah differs from premeditated murder, so no specific rules govern it (rechtsvacuum). Third, this study encourages preserving the death penalty in extraordinary crime cases. The principle of justice is the primary basis for this conclusion. This study recommends incorporating elements of Islamic criminal law as one of the elements in national law.